2020
DOI: 10.17113/ftb.58.02.20.6593
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Spectrophotometric Methods for Polyphenol and Ascorbic Acid Determination in Fruit and Vegetable Extracts

Abstract: Research background. Fresh-cut fruits and vegetables are considered sources of antioxidant compounds. However, their shelf life is limited due to nutritional, quality and safety deterioration. Therefore, in recent decades, various methods have been reported for food processing and preservation, as well as for the determination of antioxidant compounds, due to their many benefits when consumed. The aim of the present work is to compare the performance of electrochemical and spectrophotometric methods in the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The sensitivity and reusability of the biosensor were analyzed. The average values of sensitivity of the three independent measurements; the coefficient of variation of the sensitivity; and the linear range were (0.220 ± 0.002) mA mM −1 , 9%, (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) µM and (0.190 ± 0.001) mA mM −1 , 5%, (1-9) µM for the 4:1 and 20:1 composites, respectively. Both composites were used five days after their preparation to modify electrodes and to adsorb HRP from the fresh protein solution.…”
Section: Selection Of the Composite Proportion And Hrp Adsorption Met...mentioning
confidence: 94%
See 2 more Smart Citations
“…The sensitivity and reusability of the biosensor were analyzed. The average values of sensitivity of the three independent measurements; the coefficient of variation of the sensitivity; and the linear range were (0.220 ± 0.002) mA mM −1 , 9%, (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) µM and (0.190 ± 0.001) mA mM −1 , 5%, (1-9) µM for the 4:1 and 20:1 composites, respectively. Both composites were used five days after their preparation to modify electrodes and to adsorb HRP from the fresh protein solution.…”
Section: Selection Of the Composite Proportion And Hrp Adsorption Met...mentioning
confidence: 94%
“…In this regard, electrochemical biosensors represent an excellent alternative with advantages such as rapid response, specificity, minimal sample preparation, and less expensive equipment [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These substances possess many advantages including anti-aging and anti-inflammatory. Additionally, it has been suggested that they could be useful for the prevention of several chronic and neurodegenerative disorders (Zehiroglu and Ozturk Sarikaya 2019;Tulli et al 2020;Minutti-López Sierra et al 2019). Berry fruits play a significant role in human nutrition and provide numerous health benefits because of their high nutrient content, which includes vitamins, minerals, and bioactive components such polyphenolic phytochemicals (Olas 2018;Golovinskaia and Wang 2021;Cosme et al 2022).…”
Section: Introductionmentioning
confidence: 99%